Propuesta del centro del faenamiento de reses y porcinos para el cantón el Guabo, provincia de El Oro. - Rodríguez Gómez, Karen Estefanía (2015)
This paper describes the development Titling of a proposed center slaughter of cattle and pigs for El Guabo Canton, which is dedicated to providing the right service in this process and also marketing in the local market. This proposal will cover the design of a suitable slaughter duly center for this process, as well as architectural model, such as sanitary and electrical installations; it should be emphasized that what is presented is a previous model to a technical project of the same. The main objective of Labor certification is to develop a proposal that allows a design that is governed by appropriate technical standards and it can function as an element in economic and social development for food security and sovereignty of El Guabo Canton, Province Gold. The study will begin with a collection of information, which will be held with the current abattoir visits, and potential sites for implementation, observing the process as this activity is done currently. the lifting of the land will also be held. Likewise, the functionality of each of the installations that must have a center of this kind, so that meets all technical standards associated with this type of project will be analyzed.